1998
DOI: 10.1007/bf02783337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sperm viability with seminal plasma metal levels

Abstract: This study compares the semen levels of lead (Pb), cadmium (Cd), and aluminum (Al) in relation to live sperm in semen samples from 64 apparently healthy men. The measured levels were separated into live sperm count tertiles (<25% [18 subjects], 25-50% [26 subjects], and >50% [20 subjects]). The mean +/- SD for each group was calculated, and the difference between the means of the high and low tertiles were compared by ANOVA. Significant differences were observed between the high and low live sperm groups for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…It has also been reported that aluminum chloride decreases production of testicular testosterone in mice [10]. Elevated aluminum levels in spermatozoa and seminal plasma were previously shown to be correlated with decreased sperm motility [6]; however in a later study, NO levels were also shown to be increased in the related tissue of mice [10]. Interstitial macrophages in the testis are an important source of nitric oxide produced by iNOS.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been reported that aluminum chloride decreases production of testicular testosterone in mice [10]. Elevated aluminum levels in spermatozoa and seminal plasma were previously shown to be correlated with decreased sperm motility [6]; however in a later study, NO levels were also shown to be increased in the related tissue of mice [10]. Interstitial macrophages in the testis are an important source of nitric oxide produced by iNOS.…”
Section: Discussionmentioning
confidence: 88%
“…In humans, sperm cell motility was enhanced by 0.2−1.0mM of Mg 2+ , while higher concentration led to the same motility compared to control levels (Magnus et al, 1990). In sea urchin, as well as in humans, Mg 2+ has been found to increase viability of spermatozoa in dose-dependent manner (Dawson et al, 1998). Enhancing effect of Mg 2+ ions of seminal plasma on motility of spermatozoa was also found, among others, in fish (Hajirezaee et al, 2010;Bozkurt et al, 2011).…”
mentioning
confidence: 71%
“…Over the last years, concerns have increased about Al exposure and its relationship to reproductive health [9][10][11]. The decline of sperm quality and increases in infertility have been observed over recent decades [12][13][14], which suggests the involvement of environmental contributors to this phenomenon.…”
Section: Introductionmentioning
confidence: 99%